Transient loss of peripheral vision as the presentation of left atrial myxoma. - Bolo-deoku, J (1992)
A 42-year-old man developed transient loss of vision in both eyes. On echocardiography to investigate a systolic murmur and determine the potential source of emboli, a large left atrial myxoma was diagnosed. This was removed successfully leaving no visual or neurological deficit.